Maximum Security of Login Pin Data by Combining the Gifshuffle Algorithm and TCC Algorithm - Rivalri Kristianto Hondro (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
System or data security is very important in today's digital era. Various kinds of security techniques used, one of these techniques is the encoding technique by applying a number of cryptographic algorithms. The durability of cryptographic algorithms must of course be known before the algorithm is used and applied to a system or data to be secured. This study discusses the combination of the gifshuffle algorithm and the TCC algorithm for securing login pin characters